Prevalence and determinants of adolescent idiopathic scoliosis from school screening in Xiaoshan District, Hangzhou, China - Tu, Qingyu; Xu, Wenbin; Feng, Yuqi; Zhang, Zaowei; Zhuang, Wei (Frontiers in Public Health, 2025)
ObjectiveThis large-scale epidemiological study aimed to determine the prevalence and associated risk factors of Adolescent Idiopathic Scoliosis (AIS) through school-based screening in Xiaoshan District, Hangzhou, China.MethodsA prospective cross-sectional study was conducted from 2023 to 2024, involving a total of 172,127 students aged between 7 and 18 years. A two-phase screening protocol was implemented: Phase I included physical examinations (assessing shoulder asymmetry and spinal curvature) alongside the Adams Forward Bend Test (with an angle of trunk rotation [ATR] ≥ 5°), while Phase II confirmed diagnoses through radiographic evaluation (Cobb angle ≥10°). Multivariate logistic regression analysis was employed to evaluate demographic, postural, and lifestyle factors.ResultsThe overall prevalence of AIS was found to be 1.23%, with a significant gender disparity observed (female: 1.71% vs. male: 0.92%, p < 0.001). Among the initial cohort of 4,482 screen-positive cases, hospital confirmation was obtained for 422 individuals, identifying a total of 199 AIS patients (146 mild cases, 47 moderate cases, and one severe case). Key risk factors identified included female gender (odds ratio [OR] = 2.742), postural abnormalities such as kyphosis (OR = 5.741), enrollment in junior high school (OR = 0.414), prolonged sedentary behavior exceeding 8 h per day (OR = 0.231), and family history of scoliosis (OR = 0.467). Notably, the prone position test effectively reduced false-positive rates by approximately 70.3%. Twin studies indicated no significant concordance regarding AIS diagnosis among siblings (p = 0.16).ConclusionThis study establishes that the prevalence of AIS in Xiaoshan District is consistent with national data reporting an incidence rate of approximately 1.2%. It highlights specific susceptibility based on gender as well as modifiable lifestyle risks associated with this condition. The integrated screening protocol that combines postural assessment with the Adams test demonstrates clinical utility for early detection efforts in schools. These findings underscore the necessity for preventive strategies within educational settings that focus on promoting proper posture education and encouraging increased physical activity among students.